La atadura entre imagentexto y autoficción. Mecanismos de lo irrepresentable en los libros Conjunto vacío, de Verónica Gerber y Óptica sanguínea, de Daniela Bojórquez - Rodríguez-Blanco, Sergio (Confluenze. Rivista di Studi Iberoamericani, 2019)
This work analyzes the dialectical relationships between image and text as well as between reality, fiction and self-fiction in the works Conjunto Vacío (2015) by Verónica Gerber Bicceci and Óptica sanguínea (2015) by Daniela Bojórquez Vértiz. In both books, published almost at the same time in Mexico as imagetexts, the ties and looseness of their own intermediality, which moves between representable and unrepresentable, and coding and registration is able to question the representation itself, and refer to a privilege of the equivocal versus the unambiguous.